Constraints on Hours within the Firm - Labanca, Claudio; Pozzoli, Dario (Journal of Labor Economics, 2022)
Firms often impose constraints on working hours. While many believe that these constraints shape labor supply decisions, little evidence exists to support such views. We explore this relationship using linked employer-employee data on hours worked and the variation in tax rates derived from the 2010 Danish tax reform. We show that hours worked are unresponsive to individual tax changes in firms with strict constraints, whereas they respond to these changes, directly and through spillovers, in firms with looser constraints. Starting from these findings, we discuss the determinants of hours constraints, distinguishing between firms’ technologies and coordination of hours among coworkers.